Electrocortical consequences of image processing: The influence of working memory load and worry. (30th March 2017) - White, Evan J.; Grant, DeMond M.
Abstract: Research suggests that worry precludes emotional processing as well as biases attentional processes. Although there is burgeoning evidence for the relationship between executive functioning and worry, more research in this area is needed. A recent theory suggests one mechanism for the negative effects of worry on neural indicators of attention may be working memory load, however few studies have examined this directly. The goal of the current study was to document the influence of both visual and verbal working memory load and worry on attention allocation during processing of emotional images in a cued image paradigm. It was hypothesized that working memory load will decrease attention allocation during processing of emotional images. This was tested among 38 participants using a modified S1-S2 paradigm. Results indicated that both the visual and verbal working memory tasks resulted in a reduction of attention allocation to the processing of images across stimulus types compared to the baseline task, although only for individuals low in worry. These data extend the literature by documenting decreased neural responding (i.e., LPP amplitude) to imagery both the visual and verbal working memory load, particularly among individuals low in worry. Highlights: Reduced attention (i.e., Late Positive Potential [LPP] amplitude) to stimuli under visual and verbal working memory demands. Threat stimuli elicit more attention allocation under no working memory load. Threat Stimuli elicit more attention allocation under verbal working memory load. Visual working memory load impairs discrimination of threat and neutral stimuli. Reduction in attention allocation to distractor images was present in the low worry group only.